The agro-processing industry and its potential for structural transformation of the Ghanaian economy - Nkechi S. Owoo; Monica P. Lambon-Quayefio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
The paper explores the potential of Ghana's agro-processing industry in contributing to the development and structural transformation of the economy. Although the industry is not well advanced, a number of factors are discussed which make it a viable sector to lead the economy towards sustainable development. The paper documents the evolution of the agro-processing industry, in addition to its contribution to the economy. The importance of government policy and interventions in mitigating challenges faced by the industry is also discussed. Finally, value-chain processes and case studies are provided for key agro-processing sub-sectors of the industry.
Keywords: L52; L78; O14; 330; agro-processing industry; economic growth; value-chain; Ghana; case study